PENGUATAN KEGIATAN AGAMA DAN SOSIAL PADA KKN MANDIRI DI MASA PANDEMI - Rika Nur Ramadani; M. Luqman Hakim (Institut Agama Islam Tribakti Kediri, 2022)
This activity aims to strengthen religious and social activities during the Mandiri KKN period during the pandemic. Bearing in mind that during a pandemic the end of which is not yet known, the community is experiencing saturation in several fields. This activity uses the PAR (Participatory Action Research) method. Where PAR has three key variables namely, Participatory, Action (action) and Research (research). The result is that the implementation of Mandiri KKN targets four areas, namely prevention of the Covid-19 virus, religion, education, and the economy. In preventing the Covid-19 virus, Mandiri KKN Participants took steps to socialize Covid prevention together with the community, village government, and stakeholders. In the religious field, Mandiri KKN participants merge with the community, participate in existing religious activities. The education sector is in the form of tutoring, and helps in schools and Islamic boarding schools because they have formal education. In the economic sector, Mandiri KKN participants participated in rice planting, visited the rice processing industry as a provision for the creative economy, and conducted training with the agriculture and animal husbandry services to increase laying hen production. This activity recommends integration and synergy so that the resilience and social strength of the community can grow quickly during the post-pandemic recovery period in all fields.